Environmental compliance in land use planning in Germany. - Leschinski-Stechow, Karsten (TU Wien, 2016)
This paper deals with the question in what way statutory environmental objectives become considered in land use plans in Germany. The inducement for such research on environmental compliance can be found in a crucial meaning of land use planning as the very basic planning area to implement any (environmental) policy and to make a difference. This evaluation makes use of a sub-dataset of a quite broader research approach, to which the author is devoted. It comprises 197 cases distributed over eleven German federal states and form a multiple proportional layered random sample. Results do indicate that the environmental objectives in most cases are fully or partly met. But it also shows that the sealing with impervious surfaces more or less is not limited by the planning bodies. An analysis of possible influential factors does on the one hand confirm some theoretical expectation, like e.g. shrinking cities do rather apply inner city development than growing ones. On the other hand factors like the location or built up area types turned out to be meaningful for the surface sealing.
Keywords: Raumplanung; Umweltverträglichkeit; Flächennutzung; Umweltplanung; Umweltschutz; Planungsprozess; Flächenplanung; Landnutzungsplanung; Datenanalyse